Simultaneous Determination of Diazinon, Malathion and Quinalphos Pesticide Formulations by Gas Chromatography with an Electron Capture Detector - A.K, Lal; G.H, an; M.K, Chai (Malaysian Journal of Science, 2006)
A gas chromatography (GC) method has been developed to analyze simultaneously separate formulations of Diazinon, Malathion and Quinalphos with the internal standard method. A mixture of pure standard solution spiked with Chlorpyrifos as the internal standard and diluted with methanol was sonicated to homogenize the solutions. A 2µL volume of the mixture standard solution was injected into the GC-ECD and a six point calibration curve that demonstrated a linear range was established for each target compound. Samples of each formulation, mixed with the internal standard and diluted with methanol were injected into the GC-ECD. Combinations of three different concentrations of each formulated pesticide were analyzed six times to obtain coefficients of variation which are less than 1 %. The total analysis time for each run was IS minutes. The concentration of active ingredients in the pesticide formulations were calculated from the peak area values at a retention time interpolated from the calibration graphs. The analytical results which show 55.41 ± 0.82 % for Diazinon, 83.97 ± 0.36% for Malathion and 10.89 ± 0.89 % for Quinalphos were within the specifications for these commercial pesticide formulations.